Neural mechanisms of non-pharmacological interventions in patients with mild cognitive impairment and Alzheimer's disease: An ALE meta-analysis - Ning Wang; Jinkun Li; Yunxiao Guo; Panbing Zhang; Fulin You; Ziyi Wang; Zhonghuan Wang; Xiaobin Hong (Experimental Gerontology)
Non-pharmacologic interventions are effective for persons showing mild cognitive impairment (MCI) and Alzheimer's disease (AD). We used activation likelihood estimation (ALE) meta-analysis to systematically quantify the results of 19 neuroimaging studies in order to identify brain regions in which patients showed stable increases or decreases in activation after interventions. We also tested the moderating effects of disease stage (MCI vs. AD) and intervention modality (cognitive training vs. exercise intervention). The results showed increased activation in the cuneus, precuneus and medial frontal gyrus in the combined groups after treatment, whereas the anterior cingulate gyrus showed decreased activation. Secondly, in the MCI group there was increased activation in the precuneus and precentral gyrus after treatment, whereas there was decreased activation in the anterior cingulate gyrus; in the AD group there was only increased activation after treatment, including in the lingual gyrus and bilateral superior temporal gyrus. Finally, the bilateral cuneus and precentral gyrus showed increased activation after cognitive training, while bilateral insula, among others, showed decreased activation. This suggests that there are brain activation changes after non-pharmacological treatments for MCI and AD patients, but that the treatment mechanisms are moderated by stage and intervention modality. Future studies could continue to explore specific neural mechanisms involved in different intervention conditions for these patients.